Analyzing Nexus between Crude Oil, Gold, Dollar and Equity Markets with Structural Break: ARDL Evidence from India - Saji, T. G.; Joshith, V. P.; Binoy, T. A.; Sravana, K. (International Journal of Energy Economics and Policy, 2024)
This paper explores the price relations between the Crude oil, Gold, US dollar, and equities during several economic episodes. The long- and short-term causal relationships between asset markets are examined in this study. The research uses a ‘Vector Error Correction Model (VECM)’ and an ‘Autoregressive Distributed Lag (ARDL)’ bounds test to examine monthly data from April 1999 to March 2022. The results demonstrate the weak connections between asset markets throughout the different sample periods. Furthermore, the integration of most markets is uneven and changes over time. The currency and equity markets are adjusting to the long-run equilibrium only at a slow pace. We suggest that systematic risk factors must be taken into account while jointly modeling market linkages. This study improves on previous research in the subject by demonstrating the time-varying effects of asset price links on portfolio optimizations in different economic episodes.